Efforts To Improve Learning Outcomes In The Subject Of Islamic Culture History Through The Card Sort Method In Class VII-A Students Of Madrasah Tsanawiyah Negeri Jayapura - Rochmani, Nanik; Jumaeda, Siti (al-Iltizam: Jurnal Pendidikan Agama Islam, 2023)
This type of research is classroom action research which is carried out collaboratively between researchers and teachers. The research was carried out in two cycles, each cycle consisting of four components, namely planning, action, observation and reflection. Data collection techniques and tools used in this research are interviews, observation, documentation and tests. Data analysis was carried out using descriptive analysis and the Benchmark Assessment (PAP) approach by comparing student test scores against the criteria or benchmarks set by the teacher. The PAP method used by researchers uses a scoring system with a scale of 0-100. The results of learning Islamic Cultural History (SKI) on the khulafaurrasyidin leadership model material before using the Card Sort method were relatively low. It was proven that only 2 students or 14% completed the minimum completion criteria. Student learning outcomes increased, according to the results of this research in the form of increased student learning outcomes in the Islamic Cultural History (SKI) subject on the khulafaurrasyidin leadership model. During the formative test in cycle I, the students' learning completion results were 58%, with 8 students' scores and an average score of 69%, while 6 people or the other 42% were incomplete. In cycle II, students who completed almost all of the student scores were 13 people or 97% with an average class score of 88.57%. By implementing the Card Sort method, students are more enthusiastic and motivated in participating in the learning process than before.